Modified textured surface MOCVD-ZnO：B transparent conductive layers for thinfilm solar cells - 陈新亮 闫聪博 耿新华 张德坤 魏长春 赵颖 张晓丹 (半导体学报：英文版, 2014)
Modified textured surface boron-doped ZnO （ZnO：B） transparent conductive layers for thin-film solar cells were fabricated by low-pressure metal organic chemical vapor deposition （LP-MOCVD） on glass substrates. These modified textured surface ZnO：B thin films included two layers. The first ZnO：B layer, which has a pyramid- shaped texture, was deposited under conventional growth conditions, and the second layer, which has a sphere- like structure, at a relatively lower growth temperature. Typical bi-layer ZnO：B thin films exhibit a high electron mobility of 27.6 cm^2/（V.s） due to improved grain boundary states. For bi-layer ZnO：B, the haze value increases and the total transmittance decreases with the increasing film thickness of the second modification layer. When applied in hydrogenated microcrystalline silicon （μc-Si：H） thin-film solar cells, the modified textured surface ZnO：B layers present relatively higher conversion efficiency than conventional ZnO：B films.